Non-structural carbohydrate metabolism in the flesh of Stone fruits of the Genus Prunus (Rosaceae) – a review - Walker, Robert P. (2020)
Fil: Fil: Walker, Robert P. Università degli Studi di Perugia. Dipartimento di Scienze Agrarie, Alimentari e Ambientali; Italia.